Who’s Behind the Makeup? The Effects of Varying Levels of Cosmetics Application on Perceptions of Facial Attractiveness, Competence, and Sociosexuality - Aguinaldo, Erick R.; Peissig, Jessie J. (Frontiers in Psychology, 2021)
Research has demonstrated a positive effect of makeup on facial attractiveness (Cash, Dawson, Davis, Bowen, & Galumbeck, 1989; Etcoff, Stock, Haley, Vickery, & House, 2011; Russell, 2003). Makeup has also been found to influence social perceptions (Etcoff et al., 2011; Klatt, Eimler, & Kramer, 2016). While researchers have typically compared faces with makeup to faces without makeup, we propose that perceived effects will differ based on the amount of makeup that is applied. To test the effects of varying levels of makeup on perceived facial attractiveness, competence, and sociosexuality, participants assessed 35 faces with no makeup, light makeup, and heavy makeup; makeup was self-applied by participants, not applied by a makeup artist or the experimenter. Participants rated faces with makeup (either light or heavy) as more competent than those without makeup. In addition, participants rated faces with heavy makeup as significantly higher in attractiveness and sociosexuality than faces with light makeup. These results differ from previous research findings that faces with light makeup (applied by professional makeup artists) are perceived as most attractive. Our results suggest that when makeup is self-applied, faces with heavy makeup are perceived as more attractive and sociosexual than faces with light makeup, and faces with any level of makeup are rated as more competent.